2019
DOI: 10.1590/1807-1929/agriambi.v23n10p768-775
|View full text |Cite
|
Sign up to set email alerts
|

Infrared radiation drying of Moringa oleifera grains for use in water treatment

Abstract: This study aimed to evaluate the effects of using infrared radiation in the hot-air drying of Moringa oleifera grains on the inner dryer and grain temperatures, energy consumption, and grain quality. An experiment was conducted in a factorial scheme in 2013 to identify the optimum values of the air temperature (30 to 58 ºC) and infrared radiation application time (2.0 to 4.8 min) on moisture content, drying time, drying rate, inner dryer air temperature, grain temperature, energy consumption and quality of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…For example, (Jeevarathinam et al, 2021) employed infrared-assisted hot air drying to dry turmeric slices with air temperatures ranging from 50 to 70 C. This method consumed between 2.25 and 6.35 kWh of energy. Similarly, infrared radiation was used to dry Moringa oleifera grains for water treatment purposes, with IR temperatures ranging from 30 to 60 C, consuming 2.19-5.28 kWh of energy (Nascimento et al, 2019). However, recent studies have found that the air absorbs a significant proportion of energy during the drying process, reducing thermal efficiency.…”
Section: Total Energy Analysismentioning
confidence: 99%
“…For example, (Jeevarathinam et al, 2021) employed infrared-assisted hot air drying to dry turmeric slices with air temperatures ranging from 50 to 70 C. This method consumed between 2.25 and 6.35 kWh of energy. Similarly, infrared radiation was used to dry Moringa oleifera grains for water treatment purposes, with IR temperatures ranging from 30 to 60 C, consuming 2.19-5.28 kWh of energy (Nascimento et al, 2019). However, recent studies have found that the air absorbs a significant proportion of energy during the drying process, reducing thermal efficiency.…”
Section: Total Energy Analysismentioning
confidence: 99%
“…This method is simple and cost-effective, but it is marred by numerous drawbacks. These include dependence on weather conditions, prolonged drying times, and susceptibility to contamination from dust, insects, and dirt which ultimately lead to suboptimal, low-value end products [7,13,14]. Infrared (IR) drying, in contrast, is considered a more efficient method for enhancing the drying rate of agricultural products, using less energy than traditional drying methods [15].…”
Section: Introductionmentioning
confidence: 99%